Identifikasi Variasi Media Pembelajaran Yang Digunakan Guru Biologi Di SMA Negeri 5 Pekanbaru - Nur Ayu Safitri; Nurul Fauziah; Nurkhoiroh Hidayati (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Educational development in the era of the Industrial Revolution 4.0 and Society 5.0 requires the use of varied and innovative learning media, particularly in Biology learning, which involves abstract and complex concepts. This study aimed to identify the variation of learning media used by Biology teachers at SMA Negeri 5 Pekanbaru. A qualitative descriptive approach was employed using questionnaires and interviews involving three Biology teachers. Data were analyzed descriptively and inductively based on indicators of media diversity, frequency of media rotation, suitability of media to material characteristics and student needs, and creativity and sources of learning media.  The results indicated that the use of learning media variation was categorized as good to very good. Teachers utilized a combination of conventional and digital-based media, such as PowerPoint presentations, instructional videos, posters, teaching aids, and laboratory activities. However, digital media use was still dominated by presentations and videos. Therefore, the development of Augmented Reality-based learning media has strong potential to support the visualization of abstract biological concepts in a more concrete and interactive manner.